Factors Influencing the Occurrence of Preeclampsia in Pregnant Women: Literature Review - Citra Resy Ismail; Anna Sari Dewi; Muhammad Jabal Nur (Newinera Publisher, 2026)
Preeclampsia is a pathological condition characterized by an increase in blood pressure after 20 weeks of gestation, which may be accompanied by proteinuria as well as signs of organ dysfunction such as impaired liver, kidney, nervous system, and hematological function. The method used is a narrative review design of international literature from 2016–2025 obtained from Google Scholar, PubMed, ScienceDirect, ClinicalKey, and Garuda (Garba Rujukan Digital), using the keywords “preeclampsia,”“risk factors of preeclampsia,” “maternal risk factors,” “faktor risiko preeklamsia,” and “preeclampsia in pregnancy.” The results of the review indicate that preeclampsia is multifactorial, meaning it is not caused by a single factor but rather a combination of biological conditions, medical history, and maternal demographic characteristics. Medical and reproductive factors such as a history of hypertension and preeclampsia where women who previously experienced preeclampsia or have chronic hypertension have the highest risk primigravida (first pregnancy), and comorbidities such as diabetes mellitus, obesity (high BMI), and kidney disease further increase the burden on blood vessels.